Analisis Peran Pemuda Dalam Pembangunan Berdasarkan Undang-Undang Nomor 6 Tahun 2014 Tentang Desa (Studi Di Kecamatan Percut Sei Tuan Kabupaten Deli Serdang) - Irsan Armadi (Iuris Studia: Jurnal Kajian Hukum, 2020)
One of the expected roles of youth is village builder in accordance with Law No. 6/2014 on Villages. The hope is that young people take a role in rural development, especially after village funding has been distributed to the village. The research was conducted in Percut Sei Tuan District, Deli Serdang Regency. This research is a descriptive study with a qualitative approach. The method of analysis uses interview and questionnaire techniques. The purpose of this study was to analyze the implementation of village governance in Percut Sei Tuan District, Deli Serdang Regency. To analyze the role of youth in village development in Percut Sei Tuan District, Deli Serdang Regency. The results showed that the implementation of village government in the Percut Sei Tuan Subdistrict, Deli Serdang Regency, based on Law Number 6 of 2014 concerning Villages, includes the implementation of village government, empowering village communities and improving services to village communities in Percut Sei Tuan District. The role of youth in village development in Percut Sei Tuan Subdistrict, Deli Serdang Regency is that youths are tasked with carrying out development both physically and non-physically (Agent of development). Development in the physical sector of facilities and infrastructure such as roads, bridges and agriculture. Meanwhile, in the non-physical sector, it is in the form of education and counseling on Law Number 6 of 2014 concerning Villages